Comprehensive analysis of 42 psilocybin-producing fungal strains reveals metabolite diversity and species-specific clusters - Jonathan Cohen; Liron Sulimani; Shiri Procaccia; Yaniv Lerenthal; Looz Milay; Ido Taran; Anna Shapira; David Meiri (Scientific Reports)
Abstract Psilocybin-producing fungi have garnered attention due to accumulating evidence regarding the therapeutic potential of their principal component psilocybin. This diverse group of fungi harbors a wealth of less-studied metabolites, however, thus far most research has addressed them as a cohesive group. By optimizing an approach for extraction and analysis, we examined the metabolomes of 42 distinct fungi strains and show that the breadth and diversity of metabolites within and between 9 species. We integrated and validated the reproducible and reliable extraction of fruiting bodies followed by chromatographic separation, quantification and identification of their known and yet to be identified secondary metabolites. The optimal extraction of fruiting bodies for high yield of indole alkaloids was achieved using a 1:20 tissue:solvent ratio, 25:75 H2O:MeOH (pH = 9), for 1.5 h, followed by the quantification of 8 tryptophan-derived indolamines by HPLC–DAD and the identification of putative metabolite hydroxypsilocybin by HPLC–MS/MS. The metabolomic analysis revealed the diversity of metabolites within and between species. Finally, we developed and present a method that mimics the in vivo process of dephosphorylation that occurs upon ingestion for in vitro setups. Overall, our study summarizes a standardized approach for both in vitro and in vivo studies involving psilocybin-producing fungi, showcasing the unique metabolome of each strain and the rich diversity of these fungi, encompassing promising pharmaceutical potential.